THE EFFECT OF INDEPENDENT CURRICULUM E-REPORT ASSESSMENT ON ENGLISH LANGUAGE TEACHING AT SMPN SATAP 2 SANGALLA’ - Aisyah Sirajuddin, Winda; Saleka, Adi (Teaching English as a Foreign Language Overseas Journal, 2024)
The objective of this study is to find out how the English teachers assess students’ achievement from e-Report of Independent Curriculum indicator and how e-Report effect on English teachers evaluation process and the effect of Independent Curriculum e-Report assessment on English Language Teaching. In this study the researcher used a qualitative approach method and collected the data by interview and observation. The data of interview were obtained from 2 English teachers. The researcher used technique of analyzing the data of Miles and Huberman data analysis which have three phases; (1) Data Reduction, (2) Data Display (3) Conclusion Drawing/Verification and for the trustworthiness of the data, the researcher used Methodological Triangulation. The findings of this research show that there is no specific method or assessment specifically used by English teachers when assessing English subjects. Basically, the independent curriculum are still assessed in accordance with the rules, namely there is a predetermined assessment rubric and the teacher also determines the points on each aspect to be assessed then checks grammar and vocabulary. Also, the findings of this study show that e-Report greatly facilitates teachers in the assessment process. The results of this study show that according to English teachers, the effect of assessment is for teachers’ and there is also for students. The effect for students is that after they know the results of the assessment is at least they try to improve what is still lacking and determined by the interests and talents of the students themselves. The effect for teachers is how they create an atmosphere and strategies in learning English.